Development of a Data-Based Employee Recruitment Information System Web With Framework Laravel And Database Mysql On St Cetak - Rifa Ramdani; Siti Nur; Moch Irwan Hermanto (Universitas Suryakancana Cianjur, 2025)
St Cetak is a company engaged in the printing sector with production services for various print media, such as invitations, books, magazines, brochures, and other promotional materials. However, the company's recruitment system is still manual. All job application files, including curriculum vitae (CV), must be submitted in person, and communication regarding interview schedules still relies on WhatsApp. This manual approach presents several obstacles, such as the risk of document loss or damage, which ultimately slows down the employee selection process. Therefore, this study aims to design a and develop a web-based employee recruitment information system to replace the manual process currently used at St Cetak. The system development was carried out using the Software Development Life Cycle (SDLC) waterfall model, which consists of several gradual stages starting from needs analysis, system design, implementation, testing, to the maintenance stage. This system was built using the PHP programming language with the Laravel framework and MySQL as the database manager. The final result of this research is a web-based recruitment information system designed to improve the efficiency and effectiveness of the employee selection process at St Cetak. Based on the results of Blackbox testing, all system features have functioned well as planned. Temporary That, testing through method System The Usability Scale (SUS) obtained a score of 72, which is in the “Acceptable” category, so the system is declared feasible and can be used by the company.